Peran Pendidikan Agama Islam Dalam Membina Karakter Religius Siswa Sd It Cahaya Robbani Kepahiang - Nirwan Saputra; Fadillah (Yayasan Darusssalam Bengkulu, 2025)
This article discusses the important role of Islamic Religious Education in fostering religious character in elementary school students. The discussion covers two main aspects, namely the instillation of Islamic religious values as the foundation of religious character and the integration of Islamic Religious Education in the elementary school curriculum. The instillation of Islamic religious values has a crucial role in shaping the character of students who are devout, honest, tolerant, and empathetic. Values such as compassion, helping each other, and respecting fellow human beings are the core of fostering religious character. This article also reveals the importance of integrating Islamic Religious Education in the elementary school curriculum as an effort to improve understanding and appreciation of Islam comprehensively. This study uses a phenomenological approach while this type of research is qualitative research. There are three types of data collection techniques in this study, namely: Observation, Interview, and Documentation. While the data analysis techniques used are data collection, data reduction, data presentation, verification and drawing conclusions. Then the data validity checking technique used is triangulation and member check. Based on the data analysis conducted, the results of this study are: First, the role of Islamic Religious Education teachers in fostering the religious character of students at SD IT Cahaya Robbani Kepahiang